Understanding occupational health challenges in managing hospital solid waste in Zimbabwe: a critical review - Steven Jerie; Timothy Vurayayi Mutekwa; Tapiwa Shabani; Takunda Shabani; Amato Chireshe (Discover Public Health)
Abstract Industrialisation and service provision expose involved people to occupational health risks, including solid waste workers. In Zimbabwe, many concerns focus on occupational health risks affecting workers in industries, giving little attention to those involved in hospital solid waste management. This review aims to understand occupational health risks arising from hospital solid waste management in Zimbabwe, using existing literature. With a population of about 15.1 million, Zimbabwe is located in Southern Africa and shares borders with Mozambique, Zambia, Botswana and South Africa. The study employed a systematic methodology following the PRISMA framework to analyze data obtained from PubMed, Scopus, Web of Science, Google Scholar, and various websites. Results from the study showed that hospital solid waste is increasing due to outbreak and spread of diseases, population increase, disposal of outdated materials and compulsory high utilisation of disposable items. Its management is difficult since its increase overwhelms capacity of responsible authorities and a hazardous proportion worsens the challenge. Hospitals are among sources of hazardous waste including cytotoxic, radioactive, infectious, pathological, pharmaceutical and sharp waste, however non-hazardous waste includes non-contaminated materials. Hospital solid waste management strategies involves handling, storage, collection, transportation, treatment and disposal. Occupational health risks related to the activity encompass biological, psychological, physical, chemical and ergonomic risks which expose workers to acute and chronic health problems. Occurrence of risks is ascribed to lack of resources, hazardous nature of the waste, inadequate knowledge, lack of effective legal framework and insufficient research. Curbing occupational health risks require training and use of proper personal protective equipment, clear legal framework and adoption of hospital solid waste minimization strategies.